Three years (2008-2010) of measurements of atmospheric concentrations of organochlorine pesticides (OCPs) at Station Nord, North-East Greenland - Bossi, R.; Skjoth, C. A.; Skov, H. (Environmental Science: Processes & Impacts, 2013)
Atmospheric concentrations of organochlorine pesticides (OCPs) have been measured for the first time at Station Nord, North-East Greenland, from 2008 to 2010. The data obtained are reported here. Hexachlorobenzene (HCB), endosulfan I and hexachlorocyclohexanes (HCHs) were the predominant compounds detected in the atmosphere, followed by p,p'-DDE and dieldrin. Chlordane isomers and related compounds (trans- and cis-chlordanes, heptachlor and heptachlor epoxide, trans-and cis-nonachlor) were also detected. Atmospheric concentrations of the investigated compounds were correlated with temperature using the Clausius-Clapeyron equation in order to obtain information about their transport properties. The correlation between atmospheric concentrations and temperature was not significant for endosulfan I, gamma-HCH and p,p'-DDT, which indicates that direct transport from direct sources is the dominating transport mechanism for these compounds. A significant correlation with temperature was found for all the other studied pesticides and pesticide degradation products, which indicates that re-emission of these compounds from previously contaminated surfaces is an important factor for the observed variation in concentrations. Pesticide concentrations were also correlated with sea ice cover. Concentrations of the compounds that have not been in use for decades correlated with temperature and ice cover, while concentrations of compounds still in use did not correlate with either of these parameters. These observations indicate that processes such as revolatilization from the open sea surface are important mediating factors in the dynamics of anthropogenic persistent pollutants in the Arctic environment under the expected influence of climate change processes.